2002
DOI: 10.1063/1.1498884
|View full text |Cite
|
Sign up to set email alerts
|

Properties of carbon onions produced by an arc discharge in water

Abstract: A simple method to fabricate high-quality nanoparticles including spherical carbon onions and elongated fullerene-like nanoparticles similar to nanotubes in large quantities without the use of vacuum equipment is reported. The nanoparticles are obtained in the form of floating powder on the water surface following an arc discharge between two graphite electrodes submerged in water. High-resolution transmission electron microscopy ͑HRTEM͒ and scanning electron microscopy images confirm the presence of spherical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
219
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 354 publications
(230 citation statements)
references
References 18 publications
7
219
2
2
Order By: Relevance
“…These consist of a shell of about 20 curved graphene sheets surrounding a large amorphous carbon core with diameters up to 50 nm or more, distinguishing them to some extend from the present onion rings in which graphene sheets can still be recognized very close to the center of the onion structure. Such large onion structures can be formed through self-assembly of carbon atoms under electron irradiation of graphitic materials, such as polyhedral carbon particles (13,14), by thermobaric fullerene processing at 15 GPa and 1100 K (23,24) or by applying an arc-discharge between two carbon electrodes under water (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…These consist of a shell of about 20 curved graphene sheets surrounding a large amorphous carbon core with diameters up to 50 nm or more, distinguishing them to some extend from the present onion rings in which graphene sheets can still be recognized very close to the center of the onion structure. Such large onion structures can be formed through self-assembly of carbon atoms under electron irradiation of graphitic materials, such as polyhedral carbon particles (13,14), by thermobaric fullerene processing at 15 GPa and 1100 K (23,24) or by applying an arc-discharge between two carbon electrodes under water (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulated by the unique poperties and a great number of potential applications of novel carbon-related NMs, the simple method of discharge plasma in liquid was used in many experiments in last decades, by just modifying some part of the prototype, successes have been made in producing MWCNTs [280][281][282][283], carbon onions [52,[284][285][286], carbon nano horns [287,288], carbon NPs [117,118,[289][290][291][292][293][294][295], and graphene nanosheets [117,[296][297][298][299]. One example of these fabrications is presented in Fig.…”
Section: Novel Carbon-related Materialsmentioning
confidence: 99%
“…Until now, the electronic properties of the onions were characterized only by spatially resolved EELS in transmission 15,18 and reflection mode. 19 Recently Sano et al [20][21][22] reported the production of several milligrams of carbon onions with diameters ranging from 4 to 36 nm using an arc discharge between two graphite electrodes submerged in water or liquid nitrogen. It has been shown that depending upon synthesis conditions the carbon nanoparticles produced by this method contain carbon onions with a perfect spherical shape along with defective carbon onions and a minimum amount of amorphous carbon and carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%